1988
DOI: 10.1037/0022-3514.54.3.520
|View full text |Cite
|
Sign up to set email alerts
|

Sense of humor as a moderator of the relation between stressful events and psychological distress: A prospective analysis.

Abstract: Previous research has indicated that one's sense of humor serves as a moderator of the deleterious effects of negative stressful life events. However, because this research has been only cross-sectional in nature, such conclusions remain tentative. The purpose of this study was to provide for a more rigorous test of the humor as a stress-buffer hypothesis by using a prospective design that also attempted to control for the variance attributable to prior level of distress. Additionally, two measures of humor we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
113
2
5

Year Published

1993
1993
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(129 citation statements)
references
References 20 publications
7
113
2
5
Order By: Relevance
“…However, much research has been conducted concerning the associations between components of humor and psychological well-being (e.g., Kuiper et al 2004;Lefcourt and Thomas 1998;Marziali et al 2008;Olson et al 2005;Thorson and Powell 1993;Yip and Martin 2006). In general, humor seems to facilitate psychological health and well-being (Thorson et al 1997) and seems to buffer the impact of stressful life events (Nezu et al 1988). The positive relationship between sense of humor and well-being is moderated by personality constructs, for example feelings of agency and communion (Kuiper and Borowicz-Sibenik 2005).…”
Section: Humor and Well-beingmentioning
confidence: 99%
“…However, much research has been conducted concerning the associations between components of humor and psychological well-being (e.g., Kuiper et al 2004;Lefcourt and Thomas 1998;Marziali et al 2008;Olson et al 2005;Thorson and Powell 1993;Yip and Martin 2006). In general, humor seems to facilitate psychological health and well-being (Thorson et al 1997) and seems to buffer the impact of stressful life events (Nezu et al 1988). The positive relationship between sense of humor and well-being is moderated by personality constructs, for example feelings of agency and communion (Kuiper and Borowicz-Sibenik 2005).…”
Section: Humor and Well-beingmentioning
confidence: 99%
“…Earlier studies showed that adaptive components of humor, namely, affiliative and self-enhancing humor, are negatively correlated with anxiety and depression (Labbot ve Martin, 1987;Overholser, 1992;Nezu at al., 1988); while maladaptive components, namely, aggressive and self-defeating humor are positively correlated with anxiety and depression (Martin et al, 2003;Kuiper et al, 2004;Frewen et al,2008). Tucker et al (2013), stated that affiliative humor weakens the relationship between social anxiety and depression, while self-defeating humor strengthen this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Actualmente hay suficientes datos para afirmar que las emociones positivas potencian la salud y el bienestar, favorecen el crecimiento personal, permitiendo sentimientos de satisfacción con la propia vida, tener esperanza, ser optimista y percibirse más feliz (Fredrickson, 2000(Fredrickson, , 2001Fernandez-Abascal y Palmero, 1999). Incluso hay estudios que evidencian que la risa, la felicidad y el buen humor ayudan no solo a mantener sino también a recuperar la salud (Nezu, Nezu & Blissett, 1988). Existe suficiente evidencia para afirmar que las emociones positivas se relacionan con la longevidad (Danner, Snowden & Friesen, 2001), la percepción de buena salud en adultos mayores (Valliant, 2002), el desarrollo de la felicidad (Lyubomirsky, 2001), la competencia inmune (Charnetski & Brennan, 2001;Ornish, 1998), la recuperación cardiovascular y el adecuado afrontamiento al estrés y a la adversidad (Strumpfer, 2004).…”
Section: Emociones Positivasunclassified